Welfare and work in the open economy : diverse responses to common challenges in twelve countries editors, Fritz W. Scharpf, Vivien A. Schmidt. - Scharpf, Fritz W. (Fritz Wilhelm), 1935-; Schmidt, Vivien Ann, 1949- (Oxford University Press, 2000)
This text presents an in-depth analysis of the experiences of twelve countries and special studies on the participation of women in the labor market, early retirement, the liberalisation of public services, and international tax competition.